An End to Antisemitism!. - Reinhartz, Adele; Siquans, Agnethe; Mazor, Amir; Gerdmar, Anders; Lange, Armin; Levinson, Bernard M.; Berger, David; Schuller, Eileen M.; Shrenzel, Israel; Finsterbusch, Karin; Mayerhofer, Kerstin; Schmid, Konrad; et al. (An End to Antisemitism!, 2020)
This volume engages with antisemitic stereotypes as religious symbols that express and transmit a belief system of Jew-hatred. These religious symbols are stored in Christian, Muslim and even today's secular cultural and religious memories. This volume explores how antisemitic religious symbol systems can play a key role in the construction of group identities.